Wong–Zakai approximations with convergence rate for stochastic partial differential equations. Issue 5 (20th November 2018) - Nakayama, Toshiyuki; Tappe, Stefan
ABSTRACT: The goal of this paper is to prove a convergence rate for Wong–Zakai approximations of semilinear stochastic partial differential equations driven by a finite-dimensional Brownian motion. Several examples, including the HJMM equation from mathematical finance, illustrate our result.